The rhetorical emergence of culture - Meyer, Christian; Girke, Felix (Studies in rhetoric and culture, 2011)
"[A]n engaging, thought-provoking, and generative volume. Simultaneously wide-ranging and coherent, these essays explore the complex roles that rhetorical engagements - artful, resonant, and often transcending the solely verbal - play in shaping social life and the always emergent cultures at the heart of anthropological inquiry." * Don Brenneis, University of California, Santa Cruz "This volume is a welcome continuation of the Rhetoric Culture Project's efforts to bring anthropology and rhetorical studies together. It does an excellent job illustrating the way that 'culture is.